Willingness to pay and ability to pay for health care services at Zainoel Abidin public hospital Banda Aceh, Indonesia - S. Rina; M. Rosminah (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
Increasing accessibility to health care services is a prime goal in many developing countries, purposively to create an equality health care services to the populations. However, there are peoples who still do not well-utilized the provided health care provision especially due to the financial reason. Willingness-to-pay (WTP) and Ability-to-pay (ATP) are two powerful tools to measure the health care services utilization in this study, as it would present the reflection of Acehnese purchasing power for health care provision in Aceh. The purpose of this study is to determine the risk factor for healt care utilization amongst outpatient at public hospital dr.Zainoel abidin Banda Aceh. Methods: cross-sectional study involved a total of 180 outpatient captured at polyclinic public hospital dr.Zainoel abidin Banda Aceh. Survey was carried out by using a tailor-made questionnaire comprised of four separated sections; patient’s sociodemography, perception, healthcare financing and insurance coverage. Data was statistically analysed by using SPSS software and had gone trough univariate analysis and multiple logistic regression. Majority respondents (83.9%) use public health care services. Their WTP as outpatient at public health care services majority in the range less than Rp.9000 while as inpatient they were willing to pay within the range of less than Rp.30.000. However, majority (71.1%) patients expressed their ability to pay for health care services were between Rp.15.000 to Rp.219.999. Most of the  respondent do not have health insurance (64.4%). However, respondent that only able to pay less than Rp.15000 and between Rp. Rp.15000 to Rp. 219.999  for health care services have a preference of going to public health care provision rather than private to seek for health care services that is vice versa to those patients that have health insurance coverage both, patient’s ATP and possesion of health insurance coverage presented a significant different (p0.05) with the public health care utilization in this study. The public health care utilization among Acehnese is closely influenced by two factors; their abillity to pay for health care services and their possession of health care insurance